Computer-Based Monitoring and Data Management in Critical Care - Wiener, F.; Weil, M. H. (Methods of Information in Medicine, 1978)
A monitoring system which has the dual role of delivering patient care and providing a facility for clinical research requires extensive capabilities for data management, storage, and display. The system developed for the Critical Care Ward in USC's Center for the Critically 111 is described. The patient data file was designed to make maximum use of available space while maintaining flexibility and easy access for data retrieval. The contents of each patient's file is defined by the patient data outline which comprises the first record in his file. The file consists of a series of data summaries each of which combines a set of data elements logically interconnected or measured simultaneously. Disk sectors are allocated to a patient's file as the need arises. The file is concatenated by a series of location pointers. The patient data file is shared by the records of patients being monitored and those recalled from tape for data searches, with the former taking precedence when the available space is limited. The use of the patient data file in clinical research is illustrated and anticipated improvements are discussed.
Keywords: Computer-Based Monitoring; Critical Care Ward; Intensive Care; Data Retrieval